2012
DOI: 10.1007/s00423-012-0906-z
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of surgical treatment for gastric cancer patients with noncurative resection

Abstract: TG is considered to be inappropriate for the treatment of noncurative gastric cancer because of the poor prognosis, high morbidity rates, and poor compliance for chemotherapy associated with the procedure. However, noncurative DG was acceptable and postoperative chemotherapy should be used in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Several retrospective studies have reported inconsistent results depending on patient population and analytic methods. Some studies have reported significantly improved patient survival for gastrectomy plus chemotherapy compared to chemotherapy alone in carefully selected patients [173174175176177178179]. Some reports have suggested that patients with hepatic metastasis might benefit from gastrectomy plus partial hepatectomy when no other distant metastasis existed [180181182183].…”
Section: Palliative Therapymentioning
confidence: 99%
“…Several retrospective studies have reported inconsistent results depending on patient population and analytic methods. Some studies have reported significantly improved patient survival for gastrectomy plus chemotherapy compared to chemotherapy alone in carefully selected patients [173174175176177178179]. Some reports have suggested that patients with hepatic metastasis might benefit from gastrectomy plus partial hepatectomy when no other distant metastasis existed [180181182183].…”
Section: Palliative Therapymentioning
confidence: 99%
“… 2 Furthermore, some investigators suggested that a total gastrectomy should be performed in some patients because of the high morbidity rates despite a survival benefit. 9 In contrast, other studies stated that there was no survival benefit from resection in patients with non-curative factors. 6 7 The authors of these studies suggested that there might be no need for palliative gastrectomy in patients with incurable gastric carcinoma who did not have bleeding or obstruction.…”
Section: Discussionmentioning
confidence: 97%
“…Some investigators found that postoperative chemotherapy does not affect the prognosis of patients with gastric carcinoma. 9 16 In contrast, other reports showed that palliative gastrectomy combined with adjuvant chemotherapy improved the survival of patients with metastatic gastric carcinomas. 3 7 12 As the chemotherapy regimen varied throughout the current study period, we did not evaluate the survival benefits of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, it is the second most prevalent cancer in men and the fifth in women. Its incidence has decreased, but its prognosis little changed in recent years due to diagnosis made at an advanced stage of disease progression [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%